2006
DOI: 10.1161/01.atv.0000237605.25666.13
|View full text |Cite
|
Sign up to set email alerts
|

99m Tc-Annexin-V Functional Imaging of Luminal Thrombus Activity in Abdominal Aortic Aneurysms

Abstract: Background-The mural thrombus of abdominal aortic aneurysms (AAA) is involved in aneurysm progression via several interdependent biological processes including platelet activation. 99m Tc-annexin V (ANX) is a scintigraphic tracer that binds to phosphatidylserine exposed on activated platelets and apoptotic cells. Here, we evaluated the potential of ANX imaging to assess mural thrombus biological activity in an experimental AAA model. The clinical applicability was further tested ex vivo on human samples of exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
52
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 41 publications
6
52
1
Order By: Relevance
“…As proposed by some authors 5 and shown in the present study, nonbacterial and bacterial thrombotic endocarditis share common pathological consequences, mainly linked to platelet procoagulant 22,32 and proteolytic activities conveyed by thrombus formation and degradation, 12 which are greatly amplified by biological activities conveyed by the bacteria themselves. 11,33 Therefore, whatever their predominant source, platelet proaggregant and procoagulant activities participate in the development of vegetations, fibrinolytic activities contribute to sepsis diffusion and embolic potential, and numerous proteases are involved in tissue destruction in relation to their ability to damage extracellular matrix and to induce cell death.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…As proposed by some authors 5 and shown in the present study, nonbacterial and bacterial thrombotic endocarditis share common pathological consequences, mainly linked to platelet procoagulant 22,32 and proteolytic activities conveyed by thrombus formation and degradation, 12 which are greatly amplified by biological activities conveyed by the bacteria themselves. 11,33 Therefore, whatever their predominant source, platelet proaggregant and procoagulant activities participate in the development of vegetations, fibrinolytic activities contribute to sepsis diffusion and embolic potential, and numerous proteases are involved in tissue destruction in relation to their ability to damage extracellular matrix and to induce cell death.…”
Section: Discussionsupporting
confidence: 58%
“…13,15,37 Thus, radiolabeled annexin V has been used previously for in vivo scintigraphy of apoptotic cells in both animals and humans 16 -19 and acute platelet-rich 20,21 or chronically renewed mural thrombi, maintaining a permanent interface with the circulating blood. 22 Therefore, exposed phosphatidylserines can be targeted by Tc-ANX binds to and allows in vivo detection of right-and left-sided thrombotic vegetations in experimental endocarditis. Superposition of autoradiography and corresponding histological section showed that, as in the aseptic mural thrombus in abdominal aortic aneurysms, 22 annexin V predominantly binds to the most luminal layer of the vegetation, corresponding to the dynamic biologically active interface between the circulating blood components and the vegetation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although radiolabeled Annexin V may represent a promising cell-death detection technology for therapy response monitoring (9,10), outstanding problems with tumor-tobackground ratio and optimal imaging times remain for product design and clinical development. Moreover, phosphatidylserine is broadly expressed in inflamed tissue, in atherosclerotic plaques, during thrombosis (11)(12)(13)(14), and in dead noncancerous cells, which all reduce the tumor specificity of Annexin V.…”
mentioning
confidence: 99%